Non-English Department Students' Perspectives on the Use of Mobile Technology in English Language Learning Assessment - Kurniawan, Mozes (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
The use of technology is a common thing in the 21st century learning era. Educational practitioners also follow the rapid development of technology. Especially in learning English which is considered difficult to learn and master, there is one component that has a psychological effect that has the potential to suppress the optimality of student achievement. This is an assessment process carried out on the foreign language. Referring to the view that English is an important language, an idea emerged that assessment in English could be developed to be more attractive by integrating mobile technology. Therefore, this study aims to determine non-English department students' views toward mobile-based assessment in English courses. This research is descriptive qualitative research with categorization as the analysis process. By collecting, reducing and describing data, this study aims to reveal a general view of the implementation of mobile-based assessment in higher education. In general, students feel various improvements in terms of the learning process including excitement in reading and writing assessment. The use of Schoology as the mobile technology supporting learning and assessment seems to be useful as the result of this research